Development and evaluation of novel dual-target drugs encapsulated in liposome against visceral leishmaniasis - Bora K.; Kumar S.; Kanaujia S.P.; Dubey V.K. (My University, 2025)
Earlier we have reported two novel dual-target anti-leishmanial drug candidates, ZINC000008876351 and ZINC000253403245. These compounds were designed to target two crucial enzymes in the antioxidant defense system of Leishmania donovani: iron superoxide dismutase (FeSODA) and trypanothione reductase (TryR). The aim was to optimize these dual-target agents within liposomal formulations for the treatment of visceral leishmaniasis. Liposomal formulations were thoroughly characterized to confirm successful drug encapsulation. In vitro assays demonstrated that the liposome-encapsulated drugs, ZINC000253403245-liposome and ZINC000008876351-liposome, exhibited enhanced antiparasitic activity compared to their free drug counterparts. Both formulations showed significantly lower IC50 values, indicating stronger inhibition of L. donovani growth in both promastigote and amastigote stages at low micromolar concentrations. Mechanistic studies revealed that both free and encapsulated forms of the drugs induced apoptosis-like cell death in L. donovani promastigotes, as evidenced by mitochondrial membrane depolarization and phosphatidylserine externalization, assessed via flow cytometry. These results suggest that liposomal encapsulation enhances therapeutic efficacy by inducing mitochondrial dysfunction and promoting parasite death. The promising results of the ZINC000253403245-liposome and ZINC000008876351-liposome formulations highlight their potential as new, effective treatments for visceral leishmaniasis, offering a promising alternative to current therapies and representing a significant advancement in drug development for this neglected tropical disease. © 2025 Elsevier B.V.